Ocena efektywności projektów inwestycyjnych w logistycznych łańcuchach dostaw - Rodawski, Bartłomiej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Investment efficiency analysis, commonly boils down to financial appraisal of the project as a whole. However, investment project undertaken within such a complex systems as supply chains/ nets should be analyzed from different angles. In many instances financial net effect distribution analysis or economic analysis ought to be also conducted. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 418-425